Deciphering the oncogenic network: how C1QTNF1-AS1 modulates osteosarcoma through miR-34a-5p and glycolytic pathways - Yu Zhang; Hailong Lun; Naiqiang Zhu; Naiqiang Zhu; Ning Yang; Kaikai Ding; Bin Chen; Chengbing Chang; Haipeng Gu; Yanqi Liu (Frontiers in Oncology)
IntroductionOsteosarcoma (OS), a prevalent metastatic cancer among young individuals, is associated with a grim prognosis. Long non-coding RNAs (lncRNAs), including C1QTNF1-AS1, are pivotal regulators of cancer cell proliferation and motility. As an oncogene, C1QTNF1-AS1 is implicated in various tumor types, such as colorectal, pancreatic, hepatocellular carcinomas, and OS. The aim of this study was to investigate the functions and underlying mechanisms of C1QTNF1-AS1 in the progression of osteosarcoma.MethodsThis investigation focused on elucidating the functional roles and mechanisms of C1QTNF1-AS1 in OS cells. Bioinformatics tools were utilized to identify the interaction between microRNA miR-34a-5p and C1QTNF1-AS1, as well as the targeting of LDHA and PDK3 by miR-34a-5p. Dual-luciferase reporter assays and RNA immunoprecipitation were employed to validate these interactions. Expression profiles of C1QTNF1-AS1, miR-34a-5p, LDHA, and PDK3 in osteosarcoma cells were analyzed using RT-PCR and western blot analyses, revealing their intricate relationships. The impact of these molecules on OS cell proliferation, invasion, and migration was assessed through CCK-8, Transwell, and Cell scratch assay. Moreover, the effects on aerobic glycolysis in OS cells were examined by quantifying ATP levels, lactate production, glucose uptake capacity, and the extracellular acidification rate.ResultsThe findings indicated a significant decrease in C1QTNF1-AS1 expression levels in OS cells compared to normal osteoblasts. A parallel downregulation trend of miR-34a-5p was also observed in OS cells. Silencing C1QTNF1-AS1 led to a marked upregulation of LDHA and PDK3 in OS cells, which was partially attenuated by miR-34a-5p mimics. Functional evaluations demonstrated that suppression of C1QTNF1-AS1 accelerated OS cell growth, motility, invasiveness, and the Warburg effect. Conversely, the overexpression of miR-34a-5p mitigated these stimulatory effects, suggesting a regulatory role in modulating OS progression.DiscussionOur research emphasizes the critical role of C1QTNF1-AS1 in the pathogenesis of osteosarcoma (OS). We discovered that the downregulation of C1QTNF1-AS1 indirectly upregulates the expression of LDHA and PDK3 by suppressing miR-34a-5p, which functions as a regulator of the Warburg effect. This cascade of events promotes OS progression by enhancing glycolytic metabolism and supplying energy for cancer cell growth, migration, and invasion. These findings suggest a potential therapeutic target and highlight the importance of understanding the regulatory network involving lncRNAs in cancer metabolism and progression.